PIGMENTATION AND DERMAL CONSERVATIVE EFFECTS OF THE ASTONISHING ALGAE SARGASSUM POLYCYSTUM AND PADINA TENUIS ON GUINEA PIGS, HUMAN EPIDERMAL MELANOCYTES (HEM) AND CHANG CELLS - Quah, Chin Chew; Kim, Kah Hwi; Lau, Mei Siu; Kim, Wee Ric; Gundamaraju, Rohit; Gundamaraju, Rohit (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The preference for a fairer skin-tone has become a common trend among both men and women around the world. In this study, seaweeds Sargassum polycystum and Padina tenuis were investigated for their in vitro and in vivo potentials in working as skin whitening agents. Seaweed has been used as a revolutionary skin repairing agent in both traditional and modern preparations. The high antioxidant content is one of the prime reasons for its potent action. It has been employed in traditional Chinese and Japanese medicine. For centuries, most medical practitioners in the Asian cultures have known seaweed as an organic source of vitamins, minerals, fatty acids like omega-3 and omega-6 and antioxidants. The present objective of the study was to evaluate the potent dermal protective effect of the two seaweeds Sargassum polycystum and Padina tenuis on human cell lines and guinea pigs. Material and Methods: Seaweeds were extracted with ethanol and further fractionated with hexane, ethyl acetate and water. The extracts were tested for mushroom tyrosinase inhibitory activity, cytotoxicity in human epidermal melanocyte (HEM), and Chang cells. Extracts with potent melanocytotoxicity were formulated into cosmetic cream and tested on guinea pigs in dermal irritation tests and de-pigmentation assessments. Results: Both Sargassum polycystum and Padina tenuis seaweeds showed significant inhibitory effect on mushroom tyrosinase in the concentration tested. SPEt showed most potent cytotoxicity on HEM (IC50 of 36μg/ml), followed by SPHF (65μg/ml), and PTHF (78.5μg/ml). SPHF and SPEt reduced melanin content in skin of guinea pigs when assessed histologically. Conclusion: SPEt, SPHF and PTHF were able to inhibit HEM proliferation in vitro, with SPHF being most potent and did not cause any dermal irritation in guinea pigs. The results obtained indicate that SPHF is a promising pharmacological or cosmetic agent.